2023
DOI: 10.1111/vsu.13976
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative injectable opioid use and incidence of surgical site complications after use of liposomal bupivacaine in canine gastrointestinal foreign body surgery

Alexander P. Rahn,
George E. Moore,
Marije Risselada

Abstract: ObjectiveTo compare postoperative analgesic use and postoperative complications between dogs that received liposomal bupivacaine (LB) during surgical gastrointestinal foreign body (GIFB) removal and those that did not.Study designRetrospective study.AnimalsTwo hundred five dogs.MethodsMedical records for all dogs with GIFB removal at the Purdue University Veterinary Hospital between May 2017 and August 2021 were searched. Incomplete records and dogs with less than 2 weeks’ veterinary follow up were excluded. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…6,7 The off-label use of incisional infiltration of Nocita at the time of incisional closure for gastrointestinal surgery, however, is common at the authors' institutions. In a recent study, 8 the incisional complication rate (infection, seroma, and dehiscence) was 10.8% in 65 dogs that received Nocita during foreign body surgery, higher than reported for dogs that did not receive Nocita (n = 140) during foreign body surgery. The SSI rate was also higher in dogs that received Nocita, as 1.5% of the 65 dogs developed an SSI, compared to 0.7% of 140 dogs that did not receive Nocita.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…6,7 The off-label use of incisional infiltration of Nocita at the time of incisional closure for gastrointestinal surgery, however, is common at the authors' institutions. In a recent study, 8 the incisional complication rate (infection, seroma, and dehiscence) was 10.8% in 65 dogs that received Nocita during foreign body surgery, higher than reported for dogs that did not receive Nocita (n = 140) during foreign body surgery. The SSI rate was also higher in dogs that received Nocita, as 1.5% of the 65 dogs developed an SSI, compared to 0.7% of 140 dogs that did not receive Nocita.…”
mentioning
confidence: 76%
“…The SSI rate was also higher in dogs that received Nocita, as 1.5% of the 65 dogs developed an SSI, compared to 0.7% of 140 dogs that did not receive Nocita. 8 This study did not report the bacterium isolated, nor did it indicate whether dogs diagnosed with SSI had surgeries performed under clean-contaminated or dirty conditions. Another study 9 found that the incidence of wound complications after infiltration of liposomal bupivacaine in dogs did not vary significantly between clean, clean-contaminated, and dirty surgeries but that the overall wound complication rate was 19.7%, with contaminated and clean-contaminated surgeries having high complication rates of 30.8% and 23.1%, respectively.…”
mentioning
confidence: 94%